Effects of Surface Topography and Chemistry on Polyether-Ether-Ketone (PEEK) and Titanium Osseointegration. Issue 8 (15th April 2020) - Torstrick, F. Brennan; Lin, Angela S.P.; Safranski, David L.; Potter, Daniel; Sulchek, Todd; Lee, Christopher S.D.; Gall, Ken; Guldberg, Robert E.
Abstract : Study Design: An in vivo study examining the functional osseointegration of smooth, rough, and porous surface topographies presenting polyether-ether-ketone (PEEK) or titanium surface chemistry. Objective: To investigate the effects of surface topography and surface chemistry on implant osseointegration. Summary of Background Data: Interbody fusion devices have been used for decades to facilitate fusion across the disc space, yet debate continues over their optimal surface topography and chemistry. Though both factors influence osseointegration, the relative effects of each are not fully understood. Methods: Smooth, rough, and porous implants presenting either a PEEK or titanium surface chemistry were implanted into the proximal tibial metaphyses of 36 skeletally mature male Sprague Dawley rats. At 8 weeks, animals were euthanized and bone–implant interfaces were subjected to micro-computed tomography analysis (n = 12), histology (n = 4), and biomechanical pullout testing (n = 8) to assess functional osseointegration and implant fixation. Results: Micro-computed tomography analysis demonstrated that bone ingrowth was 38.9 ± 2.8% for porous PEEK and 30.7 ± 3.3% for porous titanium ( P = 0.07). No differences in fixation strength were detected between porous PEEK and porous titanium despite titanium surfaces exhibiting an overall increase in bone–implant contact compared with PEEK ( P < 0.01). Porous surfaces exhibited increased fixation strength compared with smooth and rough surfaces regardless of surface chemistry ( P < 0.05). Across all groups both surface topography and chemistry had a significant overall effect on fixation strength ( P < 0.05), but topography accounted for 65.3% of the total variance (ω 2 = 0.65), whereas surface chemistry accounted for 5.9% (ω 2 = 0.06). Conclusions: The effect of surface topography (specifically porosity) dominated the effect of surface chemistry in this study and could lead to further improvements in orthopedic device design. The poor osseointegration of existing smooth PEEK implants may be linked more to their smooth surface topography rather than their material composition. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the text In vivo analysis of smooth, rough, and porous implants possessing polyether-ether-ketone (PEEK) or titanium surface chemistry demonstrated that topography influenced osseointegration more than surface chemistry, with porous topographies exhibiting the strongest osseointegration. Overall, topography accounted for 65% of the total variance in fixation strength compared with 6% for surface chemistry.